THE FINE STRUCTURE OF PROLIFERATING CELLS IN PRENEOPLASTIC RAT LIVERS DURING AZO-DYE CARCINOGENESIS - Karasaki, Shuichi (The Rockefeller University Press, 1969)
The continuous feeding of the carcinogenic aminoazo dye DAB to rats produces hyperbasophilic foci in the preneoplastic livers. After injections of thymidine-(3)H into the rats, such foci were isolated from the livers and studied by radioautography with the phase-contrast and electron microscopes. In these foci, the only cells found to be proliferating, as determined by the uptake of thymidine-(3)H into their nuclei, were a poorly differentiated type; well differentiated hepatocytes in the same regions were not labeled with the isotope. The labeled cells had an irregular cell outline and a high nucleocytoplasmic ratio; the cytoplasm had almost completely lost the specialized elements characteristic of hepatocytes; the irregular nuclei with prominent nucleoli, the altered mitochondria, and the increased free ribosomes noted in these cells are features which are characteristic of neoplastic cells induced by DAB. Thus, it seems likely that the hyperbasophilic foci represent the sites of extensive dedifferentiation of hepatocytes followed by rapid cellular proliferation, leading to neoplastic growth.